A study on the potential of ex-mining lakes as alternative water sources - Suhaila Hani, Abu Hamid (2015)
Ex-mining lake is not favorable to be utilized as raw water source in Malaysia due to the general perception that water from this body is highly contaminated. The constituent of heavy metals in water from ex-mining lakes is the largest concern in this issue. This report focuses on a study to investigate the potential of water from mining lakes to be used as alternative raw water source for the treatment of domestic and industrial water supply and to observe the most suitable type of coagulant to be used to treat water from ex-mining lakes. In this study, the water samples were extracted from the ex-mining lakes in Bestari Jaya, Selangor. The samples were collected from three (3) different sampling points of the lakes. The lake water samples that came from the mining lakes were analyzed for three different categories of parameters; 1) physical parameter, 2) chemical parameter, 3) microbiological parameter, and tested before and after being treated by two different types of coagulants; Alum and Poly Aluminium Chloride. The physical parameters include the temperature, pH, and turbidity. The Chemical Oxygen Demand (COD), Dissolved Oxygen (DO) and heavy metals were tested under the chemical characteristics. The heavy metals that involved in this study include the Fe, Cu, Mn, Zn, Cl, Cd, and Pb. Finally, the samples were tested for the Total Coliform existence. The results showed that water from ex-mining lakes has high COD values. The concentration of Pb and Cd in the three stations exceeded the limits prescribed by the Ministry of Health (MOH), but can be eliminated using coagulation treatment using Alum and Poly-Aluminium Chloride. Based on the study, it can be concluded that water from ex-mining lakes has the potential in becoming the alternative water source in Malaysia.